Vascular contraction of umbilical arteries of pregnant women with preeclampsia - Zampieri, Gabriela Morelli [UNESP]; Nunes, Priscila Rezeck [UNESP]; Abbade, Joelcio Francisco [UNESP]; Dias-Junior, Carlos Alan [UNESP]; Sandrim, Valeria Cristina [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2024)
Objective: Potassium channels have an important role in the vascular adaptation during pregnancy and a reduction in the expression of adenosine triphosphate-sensitive potassium channels (Katp) has been linked to preeclampsia. Activation of Katp induces vasodilation; however, no previous study has been conducted to evaluate the effects of the inhibition of these channels in the contractility of preeclamptic arteries. Glibenclamide is an oral antihyperglycemic agent that inhibits Katp and has been widely used in vascular studies. Methods: To investigate the effects of the inhibition of Katp, umbilical arteries of preeclamptic women and women with healthy pregnancies were assessed by vascular contractility experiments, in the presence or absence of glibenclamide. The umbilical arteries were challenged with cumulative concentrations of potassium chloride (KCl) and serotonin. Results: There were no differences between the groups concerning the maternal age and gestational age of the patients. The percentage of smokers, caucasians and primiparae per group was also similar. On the other hand, blood pressure parameters were elevated in the preeclamptic group. In addition, the preeclamptic group presented a significantly higher body mass index. The newborns of both groups presented similar APGAR scores and weights. Conclusion: In the presence of glibenclamide, there was an increase in the KCl-induced contractions only in vessels from the PE group, showing a possible involvement of these channels in the disorder.
Keywords: Glibenclamide; Preeclampsia; Umbilical arteries; Vascular contractility